Perubahan Tekanan Darah Setelah Pemberian Anastesi Lokal Pehacain Berdasarkan Indeks Masa Tubuh - Yuwono, Budi (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Background: the use of Pehacaine local anesthetic in some people causes the change of blood pressureleading to systemic complication that may disrupt medication. This study is aimed at observing blood pressurechange post Pehacaine local anesthetic based on the Body Mass Index. Methods: the study was conducted to thepatients of oral surgery at Dental Hospital Faculty of Dentistry Jember University that needed local anesthetic usingPehacaine; epinephrine 1:80.000 2ml. The samples of study were the patients of extraction of lower jaws posteriorteeth using mandibular block local anesthetic technique. The numbers 40 of the patients was divided into 2 groupsbased on Body Mass Index, normal and obese. The data resulted were subsequently tested using t-test. Results: itshowed that the administration of Pehacaine local anesthetic increased systole blood pressure significantly in thesamples of normal and obese Body Mass Index. Conclusion: the change of systole blood pressure in the sample ofobese Body Mass Index was greater than in the normal Body Mass Index.